Tingkat Partisipasi Masyarakat dalam Perencanaan Pembangunan Daerah di Kecamatan Tidore Utara Kota Tidore Kepulauan - Sukardi Samad; Abdulrahman Senuk; Musdar Muhammad (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research was conducted with the aim of knowing the level of community participation in development planning in North Tidore Subdistrict, Tidore Islands City and to find out the factors that influence the level of community participation in development in North Tidore Subdistrict, Tidore Islands City. the research approach used in this research is descriptive qualitative research, which is a research that aims to provide a systematic, factual and accurate description of the data in the field about community participation in development planning in North Tidore Subdistrict. Data collection is done by interview, observation, literature study. Based on the results of the research conducted, it can be said that community participation in development in North Tidore Subdistrict is still classified as moderate, this can be seen from the attendance list of Musrenbang participants at the Kelurahan / Village level in North Tidore Subdistrict.